(untitled) (Scientific journal of the Fergana State University, 2024)
This article describes methods for determining the amount of vitamins of above-ground and underground parts of Rubus idaeus L. (raspberry) and Rubus caesius L. (gray blackberry) growing wild on the bank of a stream in the Fergana region, collected in the winter season. The results obtained are presented in the form of tables and diagrams. High perfomance liquid chromotography was used to determine the amount of vitamins.The results of the study wee presented in the form of tables and diagrams. When studying the composition of water-soluble vitamins, it was found that these plants have a high content of B vitamins and vitamin C.